LOVECRAFT’S TERRESTRIAL TERRORS: MORALLY ALIEN EARTHLINGS // OS TERRORES TERRESTRES DE LOVECRAFT: TERRÁQUEOS DE MORAL ALIENÍGENA - Conley, Greg (Abusões, 2017)
RECEBIDO EM 05 MAR 2017 APROVADO EM 30 MAR 2017 Lovecraft’s cosmic horror led him to create aliens that did not exist on the same moral spectrum as humanity. That is one of many ways Lovecraft’s work insists humans do not matter in the cosmos. However, most of the work on Lovecraft has focused on the space aliens, and how they are necessarily alien to humans, because they are from other worlds. Lovecraft’s terrestrial aliens, such as the Deep Ones, the Old Ones, and the shoggoths, are less alien, but just as morally strange. Lovecraft used biological horror to create his terrestrial aliens, and in turn used them to claim that morality was a product of human evolution and history. A life form with a separate evolutionarily history would necessarily have a separate and incomprehensible morality. Lovecraft illustrates that point with narrators who are ultimately sympathetic with the aliens, despite the threat they pose to the narrators and to everything they have ever known. // O horror cósmico de Lovecraft o conduziu a criar alienígenas que não existem no mesmo escopo moral da humanidade. Esta é uma das muitas formas que a literatura de Lovecraft usa para insistir que o ser humano não importa no cosmos. No entanto, a maioria dos trabalhos sobre a literatura de Lovecraft se volta para os alienígenas espaciais e como eles são considerados estranhos pelos seres humanos, devido ao fato de serem de outros planetas. Os alienígenas terrestres de Lovecraft como Deep Ones, Old Ones e Shoggoths são menos estranhos, mas tão moralmente estranhos. Lovecraft faz uso do horror biológico para criar seus alienígenas terrestres e por sua vez o usa para afirmar que a moralidade é um produto da evolução e história humana. Uma forma de vida com uma história evolutiva separada de tal conceito necessariamente possui um tipo de moralidade incompreensível e separada. Lovecraft ilustra tal ponto de vista com narradores que são em última análise simpatizantes dos alienígenas, apesar do perigo que estes representam ao narrador e a qualquer coisa que eles já conheceram. DOI: 10.12957/abusoes.2017.27816